Gender, Matrial Culture, and Identity in the Viking Diaspora - Stigsørensen, Marie Louise (Viking and Medieval Scandinavia, 2009)
Abstract As a theoretical support for the aims of theorizing the Viking Age as a diaspora, this paper reflects on the impact of diaspora on identity, especially gender. The concept of gender is considered from three positions and within the intellectual framework of gender archaeology. First, the development of a concept of gender as a fluid negotiated identity, made not given, is introduced. Thereafter the relationship between material culture and gender is considered, arguing that it is through material things and practices that gender gains substance and is experienced. Thirdly, the disruptive yet formative effects of diaspora are outlined from a gender perspective. Throughout the intellectual arguments are related to Viking-Age studies by reference to case studies within Viking-Age archaeology.